Analisis Efektivitas dan Prospek Kredit Mikro pada Baitul Qiradh di Kota Banda Aceh - Gunawan, Endra; Ramli, Muhammad Ridha (Jurnal EMT KITA, 2019)
This study aims to analyze the effectiveness and prospects of the microcredit of Baitul Qiradh in Banda Aceh City. Data gathering was carried out by distributing questionnaires to 140 customers from seven Baitul Qiradh. Furthermore, the data were analyzed descriptively using the average method. The study found that in general customers had a good assessment of microcredit channeled by the non-bank financial institutions. Unless useful to encourage the growth of their businesses, microcredit also has an impact on improving their standard of living and well-being. So that they are satisfied with the credit services they receive. Thus it can be concluded that microcredit at Baitul Qiradh in Banda Aceh not only effective for business improvement and customer welfare but also has good prospects in the future.Keywords: Baitul Qiradh, Microcredit, Efectiveness and Prospects.